2017
DOI: 10.18549/pharmpract.2017.01.839
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and use of drug information references in Utah pharmacies

Abstract: Objective:To determine which drug references Utah pharmacists use most frequently. To determine which types of drug information questions are most commonly asked, and whether Utah pharmacists have access to adequate references to respond to these questions.Methods:A 19-question survey was created using Qualtrics, LLC (Provo, Utah) software. An electronic survey link was sent to 1,431 pharmacists with a valid e-mail address listed in the Department of Professional Licensing database. Questions focused on availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…Among 8 studies conducted between 2002 and 2017, Lexicomp was the preferred drug information database in 3 studies 2,5,8 and Micromedex was the database of choice in only 1 study. 9 In the 4 remaining studies, [10][11][12][13] the Lexicomp and Micromedex databases were found to be comparable, as we observed in the current study. In our side-by-side statistical comparison of the 2 databases, we found that the Lexicomp database was rated higher on technical aspects such as layout, navigation, and speed, whereas the Micromedex product was rated higher on content aspects such as sufficiency of information and ability to solve drug-related questions.…”
Section: Discussionsupporting
confidence: 79%
“…Among 8 studies conducted between 2002 and 2017, Lexicomp was the preferred drug information database in 3 studies 2,5,8 and Micromedex was the database of choice in only 1 study. 9 In the 4 remaining studies, [10][11][12][13] the Lexicomp and Micromedex databases were found to be comparable, as we observed in the current study. In our side-by-side statistical comparison of the 2 databases, we found that the Lexicomp database was rated higher on technical aspects such as layout, navigation, and speed, whereas the Micromedex product was rated higher on content aspects such as sufficiency of information and ability to solve drug-related questions.…”
Section: Discussionsupporting
confidence: 79%
“…The most extensive change in drug information sources concerns tertiary sources with electronic accessibility and improved user-friendliness for literature search. A recent survey of pharmacies in the United States found frequent use of tertiary sources [ 22 ]. About 89% of community pharmacists and 96% of hospital pharmacists reported that available tertiary references were adequate to answer the questions they received.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the recommended sources, it is possible to submit a large number of concurrent drugs to check for interactions in an efficient way. We have previously shown that the number of drugs in the query does not influence the time spent answering it [ 20 , 22 ]. However, choice of drug interaction databases is of importance as open access drug interaction databases score statistically lower with regard to ownership, classification of interactions, primary information sources, and staff qualification [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study conducted among pharmacy students and faculty at a university in the USA also reported the high preference for Lexi-Comp for seeking information [ 9 ]. Secondly, the increased use of Micromedex was also reported from hospitals across the globe [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%